Sikap dan Kepuasan Petani terhadap Program Upaya Khusus Jagung Hibrida di Kota Kendari - Sugiharti Masri; Weka Widayati; Hartina Batoa (Universitas Halu Oleo, 2021)
This study aims to analyze the relationship between attitudes and satisfaction with the productivity of hybrid corn in Kendari City. The population in this study were 98 corn farmers. The sampling technique was carried out by simple random sampling. Determination of the number of samples using the Slovin formula. The number of samples is 50 people. The types of data used are primary data and secondary data. Data collection techniques use direct interviews with respondents and literature studies. The research variables include farmers' attitudes and satisfaction with the Hybrid Corn Special Efforts Program, corn farming productivity. The data analysis used is descriptive analysis and Rank Sperm correlation analysis. The results of the study show that the attitude of farmers towards the hybrid corn special effort program shows an average score that is positive; and high satisfaction. There is a strong correlation/relationship between farmers' attitudes and satisfaction with the special efforts of hybrid corn and corn productivity.Keywords: attitude, satisfaction, Upsus, productivity of maize